Integrasi Financial Technology Syariah Dalam Mendukung Pertumbuhan UMKM Centre Wonopringgo - Teguh Irawan; Fajar Maulana Rifky Fauzan; Faiz Mazda Niamy (JURNAL ECONOMINA, 2024)
Islamic fintech in Indonesia has grown rapidly, offering services such as peer-to-peer lending and crowdfunding aimed at meeting the needs of MSMEs. However, in Wonopringgo there remains a gap in terms of limited understanding and supporting infrastructure. This study seeks to explore the potential integration of Islamic fintech in supporting MSME growth in Wonopringgo, while also identifying the challenges and solutions required. The research applies a qualitative exploratory approach, using primary data from interviews with fintech practitioners and secondary data from journals and related literature. Data analysis was carried out using the interactive model and SWOT approach. Findings show that MSMEs often face difficulties accessing conventional financing due to collateral requirements and lengthy processes. Islamic fintech emerges as an alternative through sharia principles, unsecured capital, micro-financing, and flexible payment systems. With strong partnerships between fintechs, local institutions, and government, integration could enhance the performance of MSMEs in Wonopringgo.